Democracia e participação política na modernidade: modo filosófico de Alexis de Tocqueville e Hannah Arendt - Saliulo, João Borge Chilele (2022)
The present dissertation, which has as its theoretical framework the political philosophy of Alexis de Tocqueville and Hannah Arendt, aims to elucidate the understanding of both in the concept of democracy and of action and political participation as a necessary condition of the public sphere, also covering the notions of freedom and equality, individualism and community, and points out the institutional paths that, in the view of both authors, can ensure collective action and the plurality of citizens' opinions. And it also intends, in this trajectory, to show the strong confluences between the reflections of Tocqueville and Arendt on these questions and to verify the philosophical diligence in their efforts to recover the ideals of public spirit and participation in public life as remedies to combat the threats of despotism. emerged in modernity. But, having as object a fundamental question in the work of the two authors – the threats to democracy represented by conformism and the standardization of thought and behavior in modern societies, opening space for the despotisms that can emerge from the bosom of democracy itself –, to present what both share both common and differentiated understanding as measures to face these dangers, such as republican-democratic praxis, translated into active citizenship and the daily exercise of political freedom. Assimilate the importance of the contribution of both authors to the understanding of the phenomenon of sociopolitical development, from the associative action.